Locking in human rights in Africa: analyzing state accession to the African Court on Human and Peoples' Rights - Zschirnt, Simon (Human rights review, 2018)
The establishment of the African Court on Human and Peoples’ Rights was a pivotal moment for the African human rights system. To date, 30 of the African Union’s 55 member states have accepted the Court’s jurisdiction by ratifying the Protocol to the African Charter on Human and Peoples’ Rights on the Establishment of an African Court on Human and Peoples’ Rights. This article uses statistical analysis of state action on the Protocol to shed light upon the factors that have led some states to accept the Court’s jurisdiction and other states to thus far decline to do so. The results provide strong support for accounts of the origins of international human rights regimes that emphasize transitional states’ desire to “lock in” new commitments to democracy and human rights. Potential compliance costs, regimes’ ideological orientations, domestic legal traditions, and regional dynamics have also exerted significant effects upon the likelihood of ratification.